Review of Menstrual Hygiene Management Practices Among Adolescent Girls: Challenges, Health Implications, and Future Directions (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Although a woman's menstruation is a normal biological process that is essential to her reproductive life, managing menstrual hygiene is still a major worldwide issue, especially for teenage girls in low- and middle-income nations. Maintaining dignity and one's physical and mental health depend on practicing proper menstrual hygiene. However, barriers to good menstrual hygiene habits persist due to cultural taboos, a lack of resources, and inadequate knowledge. Examining national and international policies targeted at resolving these concerns, this analysis examines the relationship between menstrual hygiene, adolescent health, and the right to health. The conversation emphasizes how important it is to manage menstrual hygiene in an appropriate way to prevent a girl's period from interfering with her everyday activities or undermining her self-esteem. A variety of menstruation items are assessed, with a focus on choosing the right goods to preserve hygiene, including sanitary pads, tampons, menstrual cups, and period underwear. The review also touches on the effects of menstruation problems on women's lives. The support that national and international initiatives like the Swachh Bharat Abhiyan, Beti Bachao Beti Padhao (BBBP), Rashtriya Kishor Swasthya Karyakram (RKSK), and the Scheme for Promotion of Menstrual Hygiene provide for the management of menstrual hygiene and adolescent health are examined. In order to guarantee that teenage girls may have healthy, productive lives with dignity and respect, the article emphasizes the need for ongoing efforts to enhance menstrual hygiene management via education, access to sanitary products, and the breakdown of societal taboos.